Careers in business - Harding, Ben; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2003)
This program examines the huge range of jobs in the general area of'business'. Issues such as career path and options, daily duties, key skills and the pro's and con's of working for a large business are explored in interviews with three young Holden Australia employees
Title from title screen
Executive producer, Mark MaAuliffe ; editor, Jared Marshall ; sound, Wayne Martin ; camera, Kieran Doolan
Voice over: Amy Blakmur, Ben Harding
Keywords: Business -- Vocational guidance; Business; Career development